Caracterização mecânica de compósitos de matriz epóxi reforçado com fibras de sisal em diferentes orientações com auxílio da correlação digital de imagens - Mesquita, Pedro Henrique Xavier De (Universidade Federal Rural do Semi-Árido, 2018)
Composite materials are obtained by combining two or more elements, one so-called matrix, which is continuous and involves the other element, called reinforcement. The great advantage of composite confection is the possibility of obtaining a new material with properties that are not presented by the constituents. The properties of the composites depend on the characteristics of their constituents, on the relative quantity of each element, on the distribution and on the interaction between the constituent materials. The objective of this work is to evaluate the influence of chemical treatment on the mechanical properties of fiber and its composites and the influence of orientation and fiber concentration on the composites mechanical properties. The main materials used in this research were the sisal fiber obtained in its raw state and the epoxy resin. The composites were manufactured by the manual lamination technique. To obtain the results, tensile tests were performed on the fiber, resin and composites and Three-point flexural test were performed on the resin and composites. In this research, the tensile tests were aided by the digital image correlation technique, used to extract information about the deformation of the test specimens. It was observed that 2%, 5% and 8% NaOH chemical treatments promote an increase in weight loss, density and mechanical properties of the sisal fiber. The alkaline treatment also stimulated an improvement in the mechanical properties of the unidirectional composite. The results also showed that the unidirectional composites have excellent properties when tested in the fiber direction [0] and poor properties when tested orthogonally to the fiber [90]. On the other hand, the oriented composite presented the same tensile result in the two tested configurations: [90,0,0,90] and [0,90,90,0]. Oriented composites were also tested using three different fiber concentrations (10%, 20% and 30%), it was observed a growth in the final material mechanical properties as the fiber concentration was increased
Keywords: Compósitos; Fibra de sisal; Resina epóxi; Propriedades mecânicas; Correlação Digital de Imagens; Composites; Sisal fiber; Epoxy resin; Mechanical properties; Digital Image Correlation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA